2013
DOI: 10.5194/amt-6-1817-2013
|View full text |Cite
|
Sign up to set email alerts
|

Radar-radiometer retrievals of cloud number concentration and dispersion parameter in nondrizzling marine stratocumulus

Abstract: Abstract. The retrieval of cloud microphysical properties from remote sensors is challenging. In the past, ground-based radar-radiometer measurements have been successfully used to retrieve the liquid water content profile in nondrizzling clouds but offer little constraint in retrieving other moments of the cloud particle size distribution (PSD). Here, a microphysical condensational model under steady-state supersaturation conditions is utilized to provide additional constraints to the well-established radar-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…Rémillard et al () proposed a retrieval technique that is based on the combination of radar and radiometer measurements, with additional constraints being provided by a cloud condensational growth model with a lognormal cloud DSD to describe the Z profile. Rémillard et al () demonstrated that the vertical gradient of Z combined with steady state supersaturation estimates from the radar mean Doppler velocity can be used to constrain the relationship between N d and k . Subsequently, assuming that k is constant with height, they allow for N d to vary with height.…”
Section: Ground‐based Remote Sensing Approachesmentioning
confidence: 99%
“…Rémillard et al () proposed a retrieval technique that is based on the combination of radar and radiometer measurements, with additional constraints being provided by a cloud condensational growth model with a lognormal cloud DSD to describe the Z profile. Rémillard et al () demonstrated that the vertical gradient of Z combined with steady state supersaturation estimates from the radar mean Doppler velocity can be used to constrain the relationship between N d and k . Subsequently, assuming that k is constant with height, they allow for N d to vary with height.…”
Section: Ground‐based Remote Sensing Approachesmentioning
confidence: 99%
“…A fixed aspect ratio is used for each solid hydrometeor category, but for graupel and hail the empirical expression proposed by Ryzhkov et al (2011) is also available. For all model hydrometeors, the radar polarimetric variables (which depend on particle orientation) are calculated using complex scattering amplitudes from the pre-built LUTs, assuming a mean particle canting angle of 0 • (Ryzhkov, 2001) with a choice of the particle orientation distribution. The possible choices for the distribution of particle orientations are fully (three-dimensional) random orientation, random orientation in the horizontal plane, and a two-dimensional axisymmetric Gaussian distribution of orientations.…”
Section: Scattering Propertiesmentioning
confidence: 99%
“…Note the differences of the reflectivity thresholds used here and in other studies. For example, these were −15 dBZ in Sauvageot and Omar (1987), −17 dBZ in Frisch et al (1995), −19 to −16 dBZ in Wang and Geerts (2003), and −30 dBZ or lower in Kollias et al (2011). The threshold used in this study is set at the cloud base rather than for the entire cloud layer as in the abovementioned studies.…”
Section: Mathematical Backgroundmentioning
confidence: 99%